2018
DOI: 10.3928/1081597x-20180517-01
|View full text |Cite
|
Sign up to set email alerts
|

Stereopsis Simulating Small-Aperture Corneal Inlay and Monovision Conditions

Abstract: The deterioration of stereopsis and other binocular functions found in this study may be acceptable for patients who had this surgical technique because it is similar to the deterioration found in other surgical procedures of emmetropization. [J Refract Surg. 2018;34(7):482-488.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Castro et al simulated the anisocoria generated by corneal inlays using a small aperture contact lens and demonstrated a significant deterioration of stereo-acuity for near and intermediate distances [ 13 ]. Also, studies with LASIK monovision demonstrated that in a proportion of these patients, stereo-acuity is lost and that once lost, it does not recover [ 11 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Castro et al simulated the anisocoria generated by corneal inlays using a small aperture contact lens and demonstrated a significant deterioration of stereo-acuity for near and intermediate distances [ 13 ]. Also, studies with LASIK monovision demonstrated that in a proportion of these patients, stereo-acuity is lost and that once lost, it does not recover [ 11 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we demonstrated that, compared with the SACI our proposal provides images with high intensity levels. This is important because, current inlays needs to be implanted monocularly in the non-dominant eye, with the risk of significant decline in the patient's binocular visual performance, compromising stereoacuity [8], and also binocular visual acuity because binocular summation is less effective as the interocular differences in retinal image increase. In fact, Tabernero and coworkers [23] found that, the binocular far-distance visual acuity achieved with one eye implanted with SACI comply binocular summation; but, in contrast, the visual acuity for near distance seems to match to the near distance acuity of the eye with SACI.…”
Section: Discussionmentioning
confidence: 99%
“…[7]. Another visual function compromised by this inlay is stereoacuity, which could suffer a deterioration with respect to natural conditions, especially for near and intermediate distances [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the SACI produces marked interocular differences in visual latency and a Pulfrich effect [13]. Other visual function that is compromised by the SACI is a deterioration in stereoacuity with respect to natural conditions, especially for near and intermediate distances [14].…”
Section: Introductionmentioning
confidence: 99%